PROFIL PROTEIN TIGA JENIS DAGING YANG DILUMURI SERBUK DAUN PEPAYA BERBASIS SDS-PAGE - Nevi Kustia; Sri Darmawati; Fandhi Adi Wardoyo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Papaya leaves contain protease enzymes (protein decomposers), namely papain and kimopapain. Both of these enzymes have the ability to break bonds in protein molecules so that proteins break down into polypeptides and dipeptides. If working on the meat can be decomposed so that the meat becomes tender. The purpose of this study was to determine protein profiles in three types of meat before and after smeared with papaya leaf powder with 60 minutes of immersion. The protein profile of three meat types was analyzed using the SDS-PAGE method. The design of this research is descriptive research with the object of research are goat meat, buffalo and cow covered with papaya leaf powder. The result of this research shows that there are meat of buffalo, goat and cow there are many major and minor ribbon, while in buffalo meat, goat and cow which has been smeared with papaya powder there are many minor protein bands. These results indicate that papain enzyme contained in papaya leaves are powdered to break peptide bonds in meat proteins to proteins in the form of minor bands (micromolecules) and show that the higher concentration of papaya leaf powder the more denatured the protein that is on 20% concentration has only 3 protein bands.Keywords: Meat, Papaya Leaf, Protein Profile, SDS-PAGE